2020
DOI: 10.1155/2020/2587530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Arterial Hypertension on Left Atrial Size and Function

Abstract: An increase in left atrial (LA) size in patients with arterial hypertension (AHT) has long been known to be associated with worse cardiovascular morbidity and mortality contributes to various complications, including atrial arrhythmias, stroke, and heart failure. The aim of our study was to evaluate the impact of arterial hypertension (AHT) on the LA size and function. This cross-sectional investigation included one hundred patients with essential hypertension without valvular or structural heart disease and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…The LA function, including LAAEF, LAPEF, and LATEF, was decreased. These findings are in line with earlier studies showing a significant association between hypertension and LA volume and function ( 4 , 6 ). Ikejder et al ( 4 ) conducted a cross-sectional investigation on the evaluation of the relationship between hypertension and LA volume and function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The LA function, including LAAEF, LAPEF, and LATEF, was decreased. These findings are in line with earlier studies showing a significant association between hypertension and LA volume and function ( 4 , 6 ). Ikejder et al ( 4 ) conducted a cross-sectional investigation on the evaluation of the relationship between hypertension and LA volume and function.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with earlier studies showing a significant association between hypertension and LA volume and function ( 4 , 6 ). Ikejder et al ( 4 ) conducted a cross-sectional investigation on the evaluation of the relationship between hypertension and LA volume and function. Using two-dimensional echocardiography, the investigation showed increases in LA reservoir function and pump function, while the LA conduit function decreased.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As the application of STE to LA and RV has been increasingly performed for the evaluation of HF, valvular disease, hypertension, etc. [ 78 80 ] showing great feasibility regardless of the operator's experience [ 81 ], it has also recently been extended to patients with CAD.…”
Section: Other Cardiac Chambersmentioning
confidence: 99%
“…Numerous observational studies have demonstrated the prognostic utility of speckle tracking echocardiography (STE)-derived LA strain parameters in cardiovascular conditions including mitral regurgitation (MR) and hypertension. [2][3][4] In these pathologies, accurate assessment of LV dysfunction using standard parameters such as LV ejection fraction (EF) may be challenging due to the presence of LV volume loading and thus pseudo-preservation of EF until relatively late in the disease course. Moreover, echocardiographic assessment of the LA via STE has proven technically challenging to-date due non-standard acoustic windows, adjacent anatomical structures and the thin wall of the LA.…”
mentioning
confidence: 99%